Statistical approach to research of development of information society in the context of world tendencies - E. N. Klochkova (Статистика и экономика)
The current world tendencies influence also the Russian economy which has fully entered an era of forming of information society. Development and broad application of information and communication technologies is determined by a global tendency of world development and has crucial importance for increase of competitiveness of economy, expansion of opportunities of its integration into world system of economy, increase of efficiency of public administration and local self-government. Now development of information society does not have alternatives. Expansion of use of information and communication technologies is a condition of transition to new economic way, a factor of growth of quality of life of citizens and a labor productivity of economy, the instrument of protection of national interests. In recent years information and communication technologies became the effective tool in the economic relations arising in a production process, distributions, an exchange and consumption of the benefits between economic actors. Widespread introduction of information technologies in economic activity of society stimulates profound infrastructure changes in scales of all global economic space. Today the majority of the countries aims at forming of information society, and the most priority directions of development are creation of the electronic government, implementation of information technologies in education, culture and health care. Indicators of development of information society dynamically change both in the Russian Federation, and in the majority of foreign countries, competitive struggle for presence of the companies in the international market becomes tougher. Important task of further social and economic development of Russia is improvement of quality of information exchange in various spheres of activity of society on the basis ofeffective development of the sphere of information and communication technologies. In this regard actual are questions connected with an assessment of a condition and development of this sphere taking into account global tendencies of development of information society.